Kelebihan, Kekurangan, Peluang Teknologi 5G di Indonesia - Trikolas Trikolas; Aming Sungkowo; Rosyid Ridlo Al Hakim; Ariep Jaenul (Yayasan Literasi Sains Indonesia, 2022)
On May 27, 2021, Indonesia has started using the fifth-generation digital device known as 5G and officially launched in Indonesia. Currently, Indonesian people are still specifically familiar with third generation (3G) and fourth (4G) network services, and this type of 4G service is still completely unreachable in several locations in Indonesia, especially outside Java. The development of fifth generation (5G) technology in Indonesia is still not widely studied. This study aims to review of strengths and weaknesses of 5G technology in Indonesia.